2022
DOI: 10.1093/tas/txac027
|View full text |Cite
|
Sign up to set email alerts
|

Invited review: a carcass and meat perspective of crossbred beef × dairy cattle

Abstract: Crossbreeding dairy cows with beef sires has greatly altered the consist of U.S. dairy-influenced slaughter cattle and generated an influx of crossbred beef × dairy cattle to the U.S. fed beef slaughter supply in 2021. This review provides a summary of our observations of carcass and meat traits in the recent U.S. beef × dairy crossbred population and, based on these observations, exposes future opportunities for consideration. Strip loin steaks from beef × dairy cattle can be marketed alongside conventional b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Regardless of breed, the demand from dairy herds for beef semen represents a unique opportunity for genetics companies and seedstock producers to collaborate in producing beef bulls with high terminal breeding values, not just improved WBSF. The potential traceability of beef × dairy progeny has been discussed as an attribute for beef marketing by Foraker et al. (2022b) .…”
Section: Resultsmentioning
confidence: 99%
“…Regardless of breed, the demand from dairy herds for beef semen represents a unique opportunity for genetics companies and seedstock producers to collaborate in producing beef bulls with high terminal breeding values, not just improved WBSF. The potential traceability of beef × dairy progeny has been discussed as an attribute for beef marketing by Foraker et al. (2022b) .…”
Section: Resultsmentioning
confidence: 99%
“…Whilst beef from dairy breed animals tends to rate highly in terms of meat quality, red meat yield has been a primary reason for packer discounts on dairy beef. Although evidence of dairy beef being marketed at consistent premium with scale is lacking, it has been shown that beef produced from surplus dairy calves can be successfully marketed alongside conventional beef products when strategically bred and fed for pre-determined markets (Foraker et al 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Given that beef from the dairy herd already makes up a large percentage of global supply (Greenwood 2021 ; Foraker et al 2022 ) where it is largely not distinguished from beef originating from beef herds, it is unsurprising that value chain stakeholders expressed doubts over the ability to create ‘new’ markets for dairy beef in Australia. Indeed, marketing beef as dairy origin may pose additional risks, should citizens become aware that differences exist in terms of whether the calf was reared by its mother, as is the routine in the beef industry, or immediately separated, as is routine in the dairy industry (Ventura et al 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Along with that, the texture of the meat and flavor significantly influence the acceptance of the product by the consumers. The flavor from the BoD crossbreds was more butter and fat-like as compared to beef breeds [ 38 ]. The steak quality of BoD crossbreds was also found to be intermediate between dairy (lowest) and beef (highest) breeds.…”
Section: Implications Of Beef-on-dairy At the Animal Levelmentioning
confidence: 99%